An Overview of Pyridazinone Analogs: Chemical and Pharmacological Potential - Boukharsa, Youness; Karrouchi, Khalid; Attjioui, Houda; Ansar, M'Hammed (Mini Reviews in Medicinal Chemistry, 2025)
Pyridazinones are classical molecules that occupy an important place in heterocyclic chemistry, and since their discovery, they have been widely developed. The introduction of new functional groups into pyridazinone structures has enabled the synthesis of a large diversity of compounds. The pharmacological and agrochemical importance of pyridazinone derivatives has aroused the interest of chemists and directed their research toward the synthesis of new compounds with the aim of improving their biological effectiveness. In this review, we have compiled and discussed the different synthetic routes, reactivity, and pharmacological and agrochemical applications of the pyridazinone ring.
Keywords: pyridazinone